2010
DOI: 10.1111/j.1744-9987.2010.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Function, Activation and Apoptosis During and After Apheresis

Abstract: Platelets are known to undergo shape change, activation, release reaction and apoptosis/necrosis during processing and storage. Apheresis may have a deleterious impact on platelet achievability and functional integrity. Platelet concentrates from 50 male volunteers obtained by COBE spectra were screened for platelet activation (CD62 and CD154) and apoptosis (phosphatidylserine detected by Annexin V). Donor samples before separation, during apheresis and at the third day of storage were used as baseline donor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In a study of 50 male platelet concentrates screened for platelet activation, Bakry et al found a positive correlation between CD40L and Annexin V on the surface of platelets that increased during separation of platelets from whole blood and again when tracked on the third day of storage (29). A more detailed kinetic investigation of the spontaneous release of sCD40L from multiple donor pooled platelet concentrates demonstrated an increase through 72 hours and remained at those levels through 126 hours.…”
Section: Scd40l In Platelet Concentratesmentioning
confidence: 99%
“…In a study of 50 male platelet concentrates screened for platelet activation, Bakry et al found a positive correlation between CD40L and Annexin V on the surface of platelets that increased during separation of platelets from whole blood and again when tracked on the third day of storage (29). A more detailed kinetic investigation of the spontaneous release of sCD40L from multiple donor pooled platelet concentrates demonstrated an increase through 72 hours and remained at those levels through 126 hours.…”
Section: Scd40l In Platelet Concentratesmentioning
confidence: 99%
“…17 Platelets only have 45% activity towards ADP activation on day 1, and gradually decrease to 12% on day 5. 10 Similarly, another study reported that platelet aggregation response towards ADP and collagen activation decrease gradually from day 1 to day 5, from 78% to 17%. 16 Contrary to those reports, this study observed that platelets have no measurable response to ADP-induced aggregation on day 3, whilst, from earlier reports, the activity was still measurable until day 5.…”
Section: Discussionmentioning
confidence: 88%
“…8 Many researchers have argued that storing platelets in 4 °C will prevent bacterial growth and will lower the platelet metabolic rate, although it is still controversial if cold storage gives more benefit in preserving platelet responsiveness to agonist activation. 8,10,11 In this study, the platelet functions during 3 days of platelet storage was evaluated using the platelet aggregation test despite the fact that the light transmission aggregatory (LTA) is widely used as a gold standard for platelet function test. 12 Platelet aggregation evaluation is considered as the easiest and the most economical method for the purposes of platelet abnormality screening, diagnosis, monitoring therapy, predicting bleeding, and assessing stored platelet.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the protocol may appear to drive artifactual outcomes, as far as it perpetuates platelet activation, although, paradoxically, it has been designed to determine the extent of platelets' readiness to get activated. Remarkably, all the above hallmarks, presented in the course of platelets' staining with annexin V, are strictly convergent with those typical for apoptosis [215][216][217][218]. Then, it is of no wonder that merely the determination of annexin V binding might discriminate reliably apoptotic from nonapoptotic platelets.…”
Section: Blood Platelet Apoptosis-do We Need To Bother With This?mentioning
confidence: 83%